Tall Claims : Mortality Selection and the Height of Children - Alderman, Harold; Lokshin, Michael; Radyakin, Sergiy (2012)
Data from three rounds of nationally representative health surveys in India are used to assess the impact of selective mortality on children s anthropometrics. The nutritional status of the child population was simulated under the counterfactual scenario that all children who died in the first three years of life were alive at the time of measurement. The simulations demonstrate that the difference in anthropometrics due to selective mortality would be large only if there were very large differences in anthropometrics between the children who died and those who survived. Differences of this size are not substantiated by the research on the degree of association between mortality and malnutrition. The study shows that although mortality risk is higher among malnourished children, selective mortality has only a minor impact on the measured nutritional status of children or on that status distinguished by gender.